Pengaruh Pembagian Peran Kelompok dalam Pembelajaran Collaborative Problem Solving (CPS) terhadap Kemampuan Kognitif - Firda Fikri Andini; Winny Liliawati; Mimin Iryanti (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the effectiveness of the Collaborative Problem Solving (CPS) model with group role division in improving students' conceptual understanding. The research problem focuses on CPS learning that previously did not apply role division, resulting in uneven group activities. This study uses a mixed method with an embedded experimental design, where quantitative data is the main focus through concept comprehension tests, while qualitative data in the form of observations of student activities is used to reinforce the analysis results. Quantitative data analysis was performed using statistical techniques, both descriptive and inferential, to see trends, differences, or relationships between variables, while qualitative data was analyzed through reduction, categorization, and interpretation processes. The results showed that the experimental group experienced a higher increase in cognitive ability compared to the control group. The effect size value of 0.7 indicates that the effect of CPS based on group role division is moderate. Furthermore, observations show that the group roles in the experimental class were more active and responsible than those in the control group. These findings confirm that integrating CPS with effective group role sharing improves student learning outcomes and cognitive abilities, particularly in understanding complex physics topics.